First-principles study of BX-SiS (X = As, P) van der Waals heterostructures for enhanced photocatalytic performance - Ahmad, Sheraz; Din, H. U.; Sabir, S. S. Ullah; Amin, B. (The Royal Society of Chemistry, 2023)
The vertical integration of two-dimensional (2D) materials through weak van der Waals (vdW) interactions is gaining tremendous attention for application in nanotechnology and photovoltaics. Here, we performed first-principles study of the electronic band structure, optical and photocatalytic properties of vertically stacked heterostructures based on boron pnictides BX (X = As, P) and SiS monolayers. Both heterobilayers possess a stable geometry and reveal type I band alignment with a direct band gap, indicating substantial transfer of charge across the junction of the same layer. Interestingly, a redshift is found in the visible light region of the optical absorption spectra of BX-SiS heterobilayers. The comparatively larger hole mobility (14 000 cm(2) V-1 s(-1)) of BP-SiS preferably allows hole conduction in the zigzag-direction. More importantly, the excellent band edge values of the standard redox potential and smaller Gibbs free energy for the adsorption of hydrogen (& UDelta;G(H*)) make them ideal for performing the hydrogen evolution reaction (HER) mechanism under solar irradiation. These findings offer exciting opportunities for developing next-generation devices based on BX-SiS heterobilayers for promising applications in nanoelectronics, optoelectronic devices and photocatalysts for water dissociation into hydrogen to produce renewable clean energy.